Antibiotic Resistance in Pediatric Infections: Global Emerging Threats, Predicting the Near Future - Alessandra Romandini; Arianna Pani; Paolo Andrea Schenardi; Giulia Angela Carla Pattarino; Costantino De Giacomo; Francesco Scaglione (MDPI AG, 2021)
Antibiotic resistance is a public health threat of the utmost importance, especially when it comes to children: according to WHO data, infections caused by multidrug resistant bacteria produce 700,000 deaths across all ages, of which around 200,000 are newborns. This surging issue has multipronged roots that are specific to the pediatric age. For instance, the problematic overuse and misuse of antibiotics (for wrong diagnoses and indications, or at wrong dosage) is also fueled by the lack of pediatric-specific data and trials. The ever-evolving nature of this age group also poses another issue: the partly age-dependent changes of a developing system of cytochromes determine a rather diverse population in terms of biochemical characteristics and pharmacokinetics profiles, hard to easily codify in an age- or weight-dependent dosage. The pediatric population is also penalized by the contraindications of tetracyclines and fluoroquinolones, and by congenital malformations which often require repeated hospitalizations and pharmacological and surgical treatments from a very young age. Emerging threats for the pediatric age are MRSA, VRSA, ESBL-producing Enterobacteriaceae, carbapenem-resistant Enterobacteriaceae and the alarming colistin resistance. Urgent actions need to be taken in order to step back from a now likely post-antibiotic era, where simple infections might cause infant death once again.